CLINICAL PROFILE OF PATIENTS WITH RARE INHERITED COAGULATION DISORDERS: A RETROSPECTIVE ANALYSIS OF 67 PATIENTS FROM NORTHERN INDIA - Sanjeev Kumar Sharma; Suman Kumar; Tulika Seth; Pravas Mishra; Narendra Agrawal; Gurmeet Singh; Avinash Singh; Manoranjan Mahapatra; Seema Tyagi; Haraprasad Pati; Renu Saxena (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction: Inherited bleeding disorders are characterized by the absence or reduced level of clotting factors, and the clinical manifestations vary according to the type and magnitude of the deficient factor. Aim: To study the clinical presentation of these rare inherited coagulation factor disorders in a tertiary care hospital and to compare the data from those reported in other populations. Methods: Sixty-seven patients, who presented to the Department of Hematology, All India Institute of Medical Sciences, New Delhi, were evaluated retrospectively from 2005 to 2011. The tests performed included platelet count, prothrombin time (PT), activated partial thromboplastin time (aPTT), thrombin time (TT), factors assay and clot solubility test in 5 M urea. Factors VIII, IX and XI assays were aPTT based while factors II, V, VII and X assays were PT based. Results: Male to female ratio was 2:1. The median age of onset of the first episode of bleeding was at 6 months (range, from birth to 20 years) whereas the median age of presentation to our hospital was 9 years (range, 2 months to 54 years). The most common deficient factor was factor X (43.28%), followed by factor XIII deficiency (26.86%) and factor VII (10.4%). Conclusion: There is a wide gap between the initial manifestation of the bleeding disorder and first presentation to the tertiary care hospital for assessment and treatment. Factor X deficiency is the most common among these rare coagulation disorders in our population, whereas factor VII deficiency is more common in Iranian and North American population.